COSMIC-L: A Photometric Catalog of Observed Stars in the Large Magellanic Cloud - Antonio Franco; Achille A. Nucita; Francesco De Paolis; Francesco Strafella (The Astrophysical Journal Supplement Series, 2025)
The Magellanic Clouds are two nearby dwarf irregular galaxies, the study of which can help us in understanding galaxy and stellar evolution. In particular, the Large Magellanic Cloud, the larger one, contains approximately 30 billion stars at various evolutionary stages. In this work, we present a Sloan Digital Sky Survey gri -band photometric analysis based on multiple images acquired with the Dark Energy Camera, installed on the Blanco telescope at Cerro Tololo Inter-American Observatory (Chile). We performed a full image analysis and photometric calibration, resulting in a photometric catalog named COSMIC-L, consisting of 57,997,665 stars, of which 18,676,294 contain estimates for all three gri magnitudes, resulting in a completeness magnitude of ≃21 and a limiting magnitude of ≃22 in all three bands.